Desenho e cultura baiana na charge de H?lio Lage - Silva, David Ricardo de Jesus (2010)
This paper discuss about drawing as an element of cultural characterization based on the charges of H?lio Roberto Lage (1946-2006), a brazilian architect who became respectable as a graphic humorist, working in a Salvador?s newspaper (Tribuna da Bahia) between 1969 and 2006. In order to achieve our goal, the charges of the referred author were investigated, trying to realize what they could reveal about Bahia?s culture, during the period they were published, that could allow the understanding of drawing as a mean of cultural discerning of a time, a place or even the inhabitants. Besides, an arguing about the particularities of the charges as a type of graphic humor and about graphic humor in Bahia were established. Our study object was made by the charges published on the newspaper described above that refers to the characteristic elements of the Bahia?s culture.